Nutritional rickets - A hospital-based study from Southern Kerala - Krishnan, Rekha; Shanavas, A; Geetha, S; Joseph, Susy (Indian Journal of Child Health, 2017)
Objective: The aim of this study is to find the characteristics of nutritional rickets and the proportion of cases diagnosed prospectively. Methods: Details of 54 cases of nutritional rickets in the age group of 1 month-12 years diagnosed during 2013-2015 in a tertiary care teaching hospital in Kerala were collected. The criteria taken for diagnosis were clinical features, biochemical parameters such as calcium, phosphorous, alkaline phosphatase (ALP), radiological features, and response to vitamin D treatment. Vitamin D level and serum parathyroid hormone levels were collected whenever it is available. The data were then analyzed statistically. Results: Among the 54 cases analyzed, 61.11% were male. A maximum number of cases were identified in the age group of 1-2 years (44.44%). Nearly 88.89% of patients were born term. About 83.3% of patients were intermediate or dark skinned. The most common clinical feature identified was bowlegs. Radiological features were identified in 70.4% of cases. The most common biochemical abnormality noted was elevated serum ALP (83.33%). Hypocalcemic seizures were a predominant manifestation in